2019
DOI: 10.1515/ijamh-2018-0260
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of difficulties in emotion regulation on attachment styles of adolescents with conduct disorders

Abstract: Adolescence is a period of achieving emotion regulation skills. One of the main responsibilities of adolescents is to learn adaptive emotion regulation and personal autonomy. The purpose of this study was to investigate the mediating role of difficulties in emotion regulation in the attachment styles of adolescents with conduct disorders. This was a cross-sectional and correlational study. The study consisted of 105 adolescent residing in detention centers in the southeast of Iran using multi-stage random samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…In addition, no relationship was found between avoidance in both parents, cognitive reappraisal, and expressive suppression. A study by Yaghoubipoor et al (2019) discovered that Iranian juveniles reported a reduction in the difficulties of emotion regulation (e.g., acceptance of emotional awareness and limited access to emotion regulation strategies) when there is an increased sense of trust and a decreased sense of alienation from their parents.…”
Section: South Asian Countriesmentioning
confidence: 99%
“…In addition, no relationship was found between avoidance in both parents, cognitive reappraisal, and expressive suppression. A study by Yaghoubipoor et al (2019) discovered that Iranian juveniles reported a reduction in the difficulties of emotion regulation (e.g., acceptance of emotional awareness and limited access to emotion regulation strategies) when there is an increased sense of trust and a decreased sense of alienation from their parents.…”
Section: South Asian Countriesmentioning
confidence: 99%
“…Two studies included in the review did not find significant associations between trust and anxiety (20,27). In terms of links between interpersonal trust and externalizing pathology in adolescents with mental illness, Clarke and colleagues' review (19) identified some studies that did not observe significant associations between interpersonal trust and conduct disorder, externalizing problems, or delinquency (20,(28)(29)(30), and other studies that did observe significant associations (31,32). Overall, studies included in Clarke and colleagues' review (19) point to strongest links between depressive symptomology and interpersonal trust beliefs among adolescents with mental illness, but also highlight a notable need for further examination of interpersonal trust beliefs in adolescent psychiatric populations.…”
Section: Introductionmentioning
confidence: 99%